Contemporary Applications of Shariah Maxims Related to Needs and Necessities in Medical Field - Hafiz Aziz ur Rahman (Journal of Islamic and Religious Studies, 2017)
Emergence of biomedical research and innovation with an unprecedented speed has created number of opportunities and challenges for policy makers. On the one hand, it is now possible to introduce tailor-made personal medication regime for an ailing patient to offer state of the art treatments. On the other hand, several ethical and legal issues have been raised due to the complex nature of emerging technologies. Policy makers all over the world are constantly addressing these challenges by continuously upgrading their respective professional and regulatory frameworks. This article is an attempt to highlight Shariah maxims which have contemporary application in medical field. Lately, there has been a lot of interest in the debate of Shariah maxims and many scholars have used maxims-based analytical frameworks to show the dynamic application of Islamic law. This article builds upon those works by focusing on issues related to the medical field.